2012
DOI: 10.1016/j.pec.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Medical interpreters as tools: Dangers and challenges in the utilitarian approach to interpreters’ roles and functions

Abstract: Objective This study explores the tensions, challenges, and dangers when a utilitarian view of interpreter is constructed, imposed, and/or reinforced in health care settings. Methods We conducted in-depth interviews and focus groups with 26 medical interpreters from 17 different languages and cultures and 39 providers of five specialties. Grounded theory was used for data analysis. Results The utilitarian view to interpreters’ roles and functions influences providers in the following areas: (a) hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(50 citation statements)
references
References 21 publications
1
45
0
4
Order By: Relevance
“…To speak too much or too little or to give their own advice during the consultation were also signs of incredibility according to the staff. This also corresponds to previous research that has described how interpreters are conceptualised as gate keepers that control or limit the patients' narratives (Hsieh & Kramer 2012), as well as looked upon as time-consuming and impractical (Kale & Raza Syed 2010). Accordingly, the main character of the interpreter was as that of an 'intruder', not really to be trusted.…”
Section: A Problem Focused Discoursesupporting
confidence: 83%
See 1 more Smart Citation
“…To speak too much or too little or to give their own advice during the consultation were also signs of incredibility according to the staff. This also corresponds to previous research that has described how interpreters are conceptualised as gate keepers that control or limit the patients' narratives (Hsieh & Kramer 2012), as well as looked upon as time-consuming and impractical (Kale & Raza Syed 2010). Accordingly, the main character of the interpreter was as that of an 'intruder', not really to be trusted.…”
Section: A Problem Focused Discoursesupporting
confidence: 83%
“…The systematic pattern that appears is thus that language interpretation seems to be foremost a practice for satisfying the needs of the institution, rather than for the patient (see also Brisset et al 2013;Hsieh & Kramer 2012). Thus, even if the health care providers in our study emphasised that language interpretation was 'self-evident' -that is, it was seen as the patient's right to have an interpreter if they needed one -it was mainly addressed with reference to the importance of being able to carry out a good work.…”
Section: Filling the Needs Of The Institutionmentioning
confidence: 99%
“…AIS patients who received PMI services may have had an increased understanding of their diagnoses and could have asked clarifying questions to make informed decisions about topics pertaining to issues such as their stroke treatment options and rehabilitation needs 12, 13. Clinicians who engaged PMI services may have leveraged the interpreters’ role as “cultural brokers” to better understand patients’ needs and perspectives and to have more meaningful conversations on topics such as stroke risk reduction and smoking cessation 14, 15, 16. This in turn may have increased the downstream likelihood of compliance with secondary stroke prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In considering the quality of family interpretations in general medicine, Meeuwesen et al (2010) raised concerns with regard to miscommunication from changes in translation to side-talk activities. Professional medical interpreters have been found to be highly successful in remote contexts using telephone-based interpreting (Price et al, 2012); however, viewing interpreters as ‗smart technology' in face to face consultations was seen as open to possible interpersonal and ethical dilemmas (Hsieh and Kramer, 2012). Flores et al (2012) indicated the critical training period for success with omission, addition, substitution, editorialization and false fluency reduced significantly for non-trained interpreters after 100 hours of training.…”
Section: Professional Interpretingmentioning
confidence: 99%
“…Research on medical interpreting has mainly focused on general medical consultations (Meeuwesen et al, 2010;Pasquandrea, 2011) with very limited attention to date in dental consultations (Author et al, 2011). Methodologically, medical interpreting has been examined through post hoc methods such as surveys or interviews to gain participant views on the perceived success or otherwise of interpreting in healthcare settings (Hsieh and Kramer, 2012). Discourse-based approaches (Pöchhacker and Shlesinger, 2005) have been employed as both corpus-based approaches for linguistic analysis to determine interpreter accuracy (Downing, 1991) and for conversation analysis to explore the unfolding patterns of interactional activity (Bolden, 2000).…”
Section: Introductionmentioning
confidence: 99%